2015
DOI: 10.1002/j.0022-0337.2015.79.8.tb05983.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Demonstration Videos in Predoctoral Endodontic Education: Aspects Perceived as Beneficial by Students

Abstract: The aim of this study was to assess the perceived beneits of video-mediated demonstrations in learning endodontics. Participants in the study were 75 third-year students enrolled in the undergraduate dentistry program at Karolinska Institute, Stockholm, Sweden. After the endodontic preclinical course, the students were introduced to the treatment protocol in the clinic by watching two live patient-demonstrated videos. The irst video demonstrated how to communicate with the patient and perform diagnosis and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Supplementary didactic elements and additional teaching materials, such as questions stimulating reflection, recordings from similar cases, or high-quality images of the employed materials and instruments may be embedded in the video. In general, studies show that video based teaching formats are judged positively by dental students, [7][8][9] and a number of reports indicate that procedural videos may result in similar learning outcomes as hands-on demonstrations. [10][11][12][13][14] In most studies, however, video materials are used as self-study formats, without additional guidance or regulation by an instructor, 3,[11][12][13][14][15] which may lead to a certain detachment from the presented clinical case, compared to a live demonstration.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary didactic elements and additional teaching materials, such as questions stimulating reflection, recordings from similar cases, or high-quality images of the employed materials and instruments may be embedded in the video. In general, studies show that video based teaching formats are judged positively by dental students, [7][8][9] and a number of reports indicate that procedural videos may result in similar learning outcomes as hands-on demonstrations. [10][11][12][13][14] In most studies, however, video materials are used as self-study formats, without additional guidance or regulation by an instructor, 3,[11][12][13][14][15] which may lead to a certain detachment from the presented clinical case, compared to a live demonstration.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is natural that they still have difficulties in transferring information from a preclinical to a clinical setting. To overcome this challenge of interfacing theory and technique, one idea is to use videos showing real time endodontic procedures, 34 or to provide preclinical students with the opportunity of 'shadowing' more advanced-level peers in the clinical setting. On the other hand, the statistical analysis showed that questions requiring clinical scenario induced significant less number of misconceptions-which, therefore, made us to consider these types of questions valuable.…”
Section: Question 5 'Basic'mentioning
confidence: 99%
“…27 Therefore, the incorporation of procedural video demonstrations into blended learning was developed to educate students' psychomotor skills. 28 The advantages of these videos in preclinical fixed prosthodontics are standardization of content delivery, magnified and unimpeded view during demonstrations and enables the students to learn at their own pace and manner.…”
Section: Performance After Different Learning Approaches and Complexi...mentioning
confidence: 99%